A modified technique for treating swimmer puppy syndrome - Karcher, D. E. [UNESP]; Costa, R. C. [UNESP]; Prada, T. C. [UNESP]; Moraes, P. C. [UNESP]; Ramon, L. A.; Minto, B. W. [UNESP]; Dias, L. G.G.G. [UNESP] (Czech Academy of Agricultural Sciences, 2018)
Swimmer puppy syndrome is an unusual anomaly that affects dogs within the first few days or months of life. This syndrome is characterised by the inability of the animal to maintain a quadrupedal position primarily using the pelvic limbs. In some cases, the condition may also affect the thoracic limbs. Although the exact pathophysiology of this condition remains uncertain, plausible causes include alterations in the neuromuscular synapse, improper myelination or poor development of peripheral motor neurons, delayed muscle development or ventral horn neuropathy. Here, we describe our results using a modified technique for the treatment of swimmer puppy syndrome, based on immobilisation for a period of one to four weeks with the aid of microporous hypoallergenic tapes, plasters and elastic meshes. Our modified method showed clear evidence of improvements.
Keywords: Bandage; Canine; Functional immobilisation; Hyperextension; Malformation; Musculoskeletal disorder; Rehabilitation